Management of Training on the 2013 Curriculum for IPA Teachers Through Partnership Program in Boalemo District, Gorontalo Province - Wismiarti, Anik; Riyanto, Yatim; Roesminingsih, Erny (International Journal for Educational and Vocational Studies, 2019)
The purpose of the science teacher training program organized by the Ministry of Education and Culture with Empowerment of partner 1 teachers through the partnership program is to improve the ability of partner 2 teachers in understanding and applying science learning in accordance with the 2013 curriculum. The Training Method is On The Job Learning with a pattern of pairing more competent teachers (having high Teachers Competency Test/UKG scores and coming from developed regions) called partner teacher 1 with teachers deemed not competent (having low UKG scores and coming from disadvantaged areas) called partner teacher 2. The sample of this study was a science teachers' at SMP Negeri 1 Tilamuta (Middle School) and SMP Negeri 1 Wonosari, Boalemo Regency, Gorontalo Province. The results obtained, a collaborative program through partnerships in basic education teachers with training methods on work learning partner teachers in Boalemo district 2 in Gorontalo province who initially did not understand and never applied the 21st Century Learning Implementation Plan (RPP) specifically Discovery Learning learning models and models Project Based Learning (PjBl) is understood and able to implement it in the classroom even though it still feels strange. Students also become happy with the model implemented by the 2 teacher's partners in the class. The interview results show that at SMP 1 Tilamuta Boalemo, 94% of students were happy with the lessons given by the teacher. While in SMP 1 Wonosari Boalemo as many as 90% of students said they were happy with sustainable learning.